2020
DOI: 10.3390/mi11040443
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of a Dilute Suspension of Aggregates in Shear-Thinning Fluids

Abstract: The prediction of the viscosity of suspensions is of fundamental importance in several fields. Most of the available studies have been focused on particles with simple shapes, for example, spheres or spheroids. In this work, we study the viscosity of a dilute suspension of fractal-shape aggregates suspended in a shear-thinning fluid by direct numerical simulations. The suspending fluid is modeled by the power-law constitutive equation. For each morphology, a map of particle angular velocities is obtained by so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This would need, at each time step, the calculation of the particle angular velocity from the solution of the set of equations presented in the previous section (as discussed above, the translational dynamics is irrelevant). Instead of directly solving the governing equations to compute the orbit, we can greatly speed-up the calculations by precomputing a database of particle translational and angular velocities for different orientations of the aggregate [35,36]. The velocities needed at the right-hand side of Equations (10) and (11) are, then, obtained by interpolating the data of the database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would need, at each time step, the calculation of the particle angular velocity from the solution of the set of equations presented in the previous section (as discussed above, the translational dynamics is irrelevant). Instead of directly solving the governing equations to compute the orbit, we can greatly speed-up the calculations by precomputing a database of particle translational and angular velocities for different orientations of the aggregate [35,36]. The velocities needed at the right-hand side of Equations (10) and (11) are, then, obtained by interpolating the data of the database.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the aggregate orbit can be reconstructed by transforming the force from the body to the lab reference frame, i.e., by rotating the aggregate according to the rotation matrix that, at every instant, transform f in F = (F, 0, 0) (that is the applied force in the lab frame). The procedure summarized in Algorithm 1 has been adopted to simulate the rheology of a dilute suspension of fractal aggregates in shear-thinning fluids and validated by reproducing the dynamics of spheroids in shear flow [36].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the effect of the non-Newtonian properties of the solvent on the viscosity of the suspension, Trofa and D'Avino 6 showed that power-law index affected intrinsic viscosity using fractal-shape aggregates in shear flow. Tanaka et al 7 found that the non-Newtonian properties of the solvent affected the relative and intrinsic viscosity of the suspension in a flow field in which the particles are homogeneously distributed.…”
Section: Introductionmentioning
confidence: 99%
“…5 In these processes, aggregates are exposed to shear, which directly affects their size and structure, 6−8 thus affecting the overall suspension properties, such as its rheology. 9 When an aggregate is introduced in shear flow, it restructures so that particle contacts within the aggregate balance the external action of the flow. The aggregate breaks when force equilibrium cannot be achieved.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Consequently, aggregate properties, such as size and structure, govern the efficiency of many industrial processes, including polymer manufacturing, wastewater treatment, , mineral processing, and liquid metal treatments . In these processes, aggregates are exposed to shear, which directly affects their size and structure, thus affecting the overall suspension properties, such as its rheology . When an aggregate is introduced in shear flow, it restructures so that particle contacts within the aggregate balance the external action of the flow.…”
Section: Introductionmentioning
confidence: 99%